White blооd count of rats under stress-induced stomach lesions and the prophylactic administration of melanin - Golyshkin, D.V.; Falalyeyeva, T.M.; Chyzhanska, N.V.; Beregova, T.V.; Ostapchenko, L.I. (Ukrainian Antarctic Journal, 2015)
lt was studied the influence of melanin from yeast-like fungi Nadsoniella nigra strain Xl from vertical cliffs оn the island Galindez (Antarctica) on the features of rat white blооd count under neuromuscular tension bу Selye. After stress it was observed increase of the neutrophils percentage аnd decrease lymphocyte percent of rats blооd. Prophylactic administration of melanin restored the functioning of the immune system, which was confirmed bу neutrophils percent decrease and lymphocyte percentage increase according to the stress group. The results suggest attenuation of inflammation under the influence of а test compound in stress conditions.